Konflik dan Rekonsiliasi dalam Jemaat Mula-Mula: Pasca Yesus dan Perjuangan Antar Para Rasul - Novi Novi (Jurnal Teologi Amreta (ISSN: 2599-3100), 2023)
This journal explores the conflicts that occurred among the apostles in the early church after the departure of Jesus and the reconciliation efforts made to maintain the unity and integrity of the church. In this paper, we present an in-depth analysis of the sources of the conflict, its impact on the congregation, and the steps taken by the apostles to overcome differences and achieve reconciliation. This research is based on an analysis of literature and relevant historical sources, such as the New Testament books and early church historical records. Qualitative Research: The research methods used may vary depending on the focus of the research, availability of data sources, and preferences of the researcher. The combination of several research methods above can also be used to gain a more comprehensive understanding of conflict and reconciliation in the early church.